Re-examining the History of Human Resource Development Policy in China: From Local Indigenous Phenomena to Global Human Resource Development Knowledge. Issue 1 (February 2022) - Wang, Greg G.; Doty, D. Harold; Yang, Shengbin
Problem: The NHRD conception claimed to be based on multiple country-cases through a constructive/interpretive process. However, four of cases focusing on HRD policy in China presented incomplete history of China's HRD policies, which may have misled the NHRD conception. Solution: We re-examine China's history of HRD policy as indigenous phenomena in comparison to the four China-cases. Adopting a similar historical method, we fail to identify the policy pattern reported by the previous cases, thus challenge the NHRD's constructivist embeddedness. We question the credibility and trustworthiness of the country-based studies as well as the sense-making constructive base of the NHRD ideation. From China's local phenomenon, we derived a set of HRD assumptions contrary to the existing western-centric assumptions to enrich the global HRD knowledge. Stakeholders: Theory-minded HRD scholars intended for rigorous and relevant theory development inquiries; practice-oriented HRD practitioners, especially those from western context and working in a non-western HRD context.